O uso de memes no ensino de história na construção de uma educação antirracista: - FARIAS, Leiliane Borges. (Universidade Federal do Tocantins, 2024)
This dissertation was developed from a didactic proposal of using internet memes to build critical learning. Thus, in the weaving of the readings carried out, in the discussions, exercises and production of memes, historical knowledge was mediated with the students, related to the theme of African slavery in Brazil, with the purpose of promoting the construction of an anti-racist education from the problematization of some internet memes as elements that represent a permanence of racism in contemporary times. The situations and mediation of these activities occurred in a 9th grade class at Escola Municipal Dr. Simão Lutz Kossobutzki, from Araguaína – Tocantins. All the efforts made to carry it out aimed to provide bases that would allow each student to develop a critical reflection, since man is a social being. In this sense, the theoretical foundations and exercises were applied so that they could follow a path towards the historical ideas of the students, using the methodology of action research, carrying out the necessary mediations, provoking discussions based on the use of memes with a racist theme, later the final product of this research gave students the opportunity to play a leading role in the production of memes that portray the deconstruction of racist ideas, debates, reports of critical learning so that the appropriation of the learning of the research subjects becomes visible and later the measurement of the results is carried out. results.